Synergistic combination of baicalein and rifampicin against Staphylococcus aureus biofilms - Muniyasamy, Rajeshwari; Manjubala, I. (Frontiers in Microbiology, 2024)
Staphylococcus aureus, a Gram-positive bacterium, is a predominant pathogen associated with various infections. The rapid emergence of antibiotic resistance has intensified the challenge of managing fracture-related infections in severe osteoporotic patients. Rifampicin, a potent antimicrobial agent employed against fracture and implant-related infections, necessitates combination therapies due to its susceptibility to antibiotic resistance. In this study, we explored the potential of baicalein, a bioactive flavonoid from Oroxylum indicum and Scutellaria baicalensis, in combination with rifampicin against S. aureus biofilms invitro. The minimum inhibitory concentration of baicalein and rifampicin were determined as 500 µg/mL and 12.5 ng/mL respectively. The synergistic activity of baicalein and rifampicin was determined by the fractional inhibitory concentration index (FICI) using checkerboard assay. The results showed the FICI of baicalein and rifampicin was lesser than 0.5, demonstrating synergistic effect. Furthermore, the efficacy of baicalein and rifampicin, both individually and in combination, was evaluated for biofilm inhibition and eradication. Scanning electron microscopy and confocal laser microscopy also confirmed that the synergistic combinations effectively removed most of the biofilms and partially killed S. aureus. In conclusion, the findings demonstrate that baicalein is as effective as rifampicin in inhibiting and eradicating S. aureus biofilms. Their combination exhibits synergistic effect, enhancing their bactericidal effect in completely eradicating S. aureus biofilms. The findings of this research underscore the research potential of combining baicalein and rifampicin as a novel therapeutic strategy against S. aureus biofilms, offering a promising direction for future research in the treatment of fracture-related S. aureus infections.